Unlocking the microbial potential of Frieseomelitta varia pollen for innovative probiotic mead development - Moutinho, Mariana Moura; Santos, Diego Coelho Barroso dos; Silva, Clara Katharina Vaz da; Paz, Ana Luísa Kruschewsky da; Rodrigues, Brenda Patricia dos Santos; Passos, Jordana Marília Soares; Suarez, Paulo Anselmo Ziani; Ghesti, Grace Ferreira; Carmo, Talita Souza (Food Science and Technology, 2025)
This study explores an innovative approach to mead production by incorporating Frieseomelitta varia bee pollen as a microbial starter to promote probiotic fermentation. Mead was produced using 5 kg of honey (82° Brix, pH 4.5), 26 L of filtered water, 20 g of pollen for lactic fermentation, and 10 g of Saccharomyces cerevisiae (M05 Mead Yeast) for alcoholic fermentation. A total of six sanitized fermentative reactors were used with varied pollen concentrations (1–20 g/2 L). The process included wort preparation (boiling, cooling, and mixing), 24 days of fermentation, 2 months of maturation, and final bottling. Samples were analyzed using standardized methods for alcohol content, pH, original and final gravity, color (ultraviolet–visible [UV–vis], 430 nm), and volatile profiles (gas chromatography-mass spectrometry [GC-MS]). Sensory evaluation assessed aroma and flavor on a 1–5 scale. The results showed that F. varia pollen supports microbial activity, yielding a mead with probiotic counts above 10⁶ colony-forming unit (CFU) mL⁻¹. The addition of pollen enhanced physicochemical characteristics and sensory properties, producing a probiotic mead with potential health benefits. This approach not only improves product quality but also aligns with growing market interest in functional and fermented beverages.